Hydroxypropyl Starch Nanoparticles as Controlled Release Nanocarriers for Piperine - Chin, Suk Fun; Asniar, Binti Salim; Pang, Suh Cem (University of Kashan, 2020)
Hydroxypropyl starch was synthesized by modified sago starch with hydroxypropylation reaction. Hydroxypropyl starch nanoparticles with mean particle sizes of 110 nm are obtained by controlled precipitation through the drop-wise addition of dissolved hydroxypropyl starch solution into excess absolute ethanol. Piperine was loaded onto hydroxypropyl starch nanoparticles and native starch nanoparticles via the in-situ nanoprecipitation process. Hydroxypropyl starch nanoparticles exhibited higher piperine loading capacity as compared to native starch nanoparticles with the maximum loading capacity of 0.46 and 0.33 mg.mg-1, respectively. Piperine was release from hydroxypropyl starch nanoparticles in a slow and sustained manner at pH 1.2 over the period of 24 hours. Whereas piperine was completely released from native starch nanoparticles within 16 hours.